Neuregulin 1 Reduces Motoneuron Cell Death and Promotes Neurite Growth in an in Vitro Model of Motoneuron Degeneration - Mòdol-Caballero, Guillem; Santos, Daniel; Navarro, Xavier; Herrando-Grabulosa, Mireia (Frontiers in Cellular Neuroscience, 2018)
Amyotrophic Lateral Sclerosis (ALS) is a devastating neurodegenerative disorder with no effective treatment currently available. Although the mechanisms of motoneuron death are still unclear, glutamate excitotoxicity and neuroinflammatory reaction are two main features in the neurodegenerative process of ALS. Neuregulin 1 (NRG1) is a trophic factor highly expressed in motoneurons and neuromuscular junctions. Several recent evidences suggest that NRG1 and their ErbB receptors are involved in ALS. However, further knowledge is still needed to clarify the role of the NRG1-ErbB pathway on motoneuron survival. In this study we used an in vitro model of spinal cord organotypic cultures subject to chronic excitotoxicity caused by DL-threo-β-hydroxyaspartic acid to characterize the effect of NRG1 on motoneuron survival. Our results show that addition of recombinant human NRG1 (rhNRG1) to the medium significantly increased motoneuron survival through the activation of ErbB receptors which was ablated with lapatinib, an ErbB inhibitor, and reduced microglial reactivity overcoming the excitotoxicity effects. rhNRG1 activated the pro-survival PI3K/AKT pathway and restored the autophagic flux in the spinal cord culture. Moreover, addition of rhNRG1 to the medium promoted motor and sensory neurite outgrowth. These findings indicate that increasing NRG1 at the spinal cord is an interesting approach for promoting motoneuron protection and regeneration.